Hubungan Tingkat Pendidikan Dengan Respon Terhadap Kehilangan Pada Pasien Abortus - Nurhidayah, Catur Desi; Sumarwati, Made; Hartati, (Jurusan Keperawatan FIKES UNSOED, 2008)
Loss and grief are human experience which are universal and unique individually. Loss could happen when someone or something couldnÃ¢â‚¬â„¢t see and someoneÃ¢â‚¬â„¢s have respond to loss was difference. The aim of this study was to know the relations between educationÃ¢â‚¬â„¢s level with response to abortionÃ¢â‚¬â„¢s patient.Analytic descriptive with correlation study approach. Samples are taken from 31 people that fulfilled the inclusive criteria with total samples method about 2 months (December 2007 - January 2008) at RSUD Purbalingga and RSU Banyumas maternity room. The researchÃ¢â‚¬â„¢s instrument used questioner which were validity and reliabilities tested. Data processing use correlation coefficient of Spearman Rank statistical test.RespondenÃ¢â‚¬â„¢s Majority was in an adequate loss category (93,55%), and the other (6,45%) had quite heavy loss. The result of correlation coefficient of Spearman Rank statistical test got ÃÂvalue = 0,263, with Assymp. Sign = 0,153, this value was bigger than a = 0,05, which means statistically there wasnÃ¢â‚¬â„¢t influence between educationÃ¢â‚¬â„¢s level with respond to losing of abortionÃ¢â‚¬â„¢s patient, so the research hypothesis of Ho accepted and Ha refused.There wasnÃ¢â‚¬â„¢t relation between educationÃ¢â‚¬â„¢s level with respond to losing of abortionÃ¢â‚¬â„¢s patient.Ã‚Â